Comics versus art - Beaty, Bart (Univ. of Toronto Press, 2012)
Introduction: Out of the historical dustbin : comics and the hierarchy of genres -- What if comics were art? Defining a comics art world -- Roy Lichtenstein's tears : Ressentiment and exclusion in the world of pop art -- Searching for artists in the entertainment empire -- Cartoons as masterpieces: an essay on illustrated classics -- Highbrow comics and lowbrow art? The shifting contexts of the comics art object -- On junk, investments, and junk investments: the evolution of comic book collectables -- Crumbs from the table: the place of comics in art museums -- By way of conclusion : Chris Ware's Comics about art